2005
DOI: 10.1001/jama.293.19.2343
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Celiac Disease Autoimmunity and Timing of Gluten Introduction in the Diet of Infants at Increased Risk of Disease

Jill M. Norris

Abstract: ELIAC DISEASE, ALSO CALLED gluten-sensitive enteropathy, is characterized by chronic inflammation in the small intestine, resulting in villous atrophy and flattening of the mucosa, induced by prolamins (gluten) present in wheat, barley, or rye. 1,2 The classic form of celiac disease typically presents in early childhood with abdominal pain and diarrhea, malabsorption, and nutrient deficiencies. Most patients with celiac disease carry the human leukocyte antigen HLA-DRB1*03 allele (usually associated with HLA-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
336
5
17

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 385 publications
(378 citation statements)
references
References 36 publications
6
336
5
17
Order By: Relevance
“…The specificity of the anti-tTG Ab is not significantly different from that of the anti-endomysium antibody, but we prefer it because it requires fewer operators. The gold standard for diagnosis is histopathology of biopsy specimens, accompanied by clinical and histological response to a gliadin-free diet and then recurrence of histological findings after the gliadin rechallenge test, which is particularly important for children below 2 years of age (9,23,24) . This method of confirmation is difficult for everyone.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the anti-tTG Ab is not significantly different from that of the anti-endomysium antibody, but we prefer it because it requires fewer operators. The gold standard for diagnosis is histopathology of biopsy specimens, accompanied by clinical and histological response to a gliadin-free diet and then recurrence of histological findings after the gliadin rechallenge test, which is particularly important for children below 2 years of age (9,23,24) . This method of confirmation is difficult for everyone.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding feeding as a single factor did not appear to be the major risk factor. Dietary gluten exposure earlier than 3 months or later than 6 months of age was found to be a risk factor in a longitudinal follow up study of a cohort of children in Denver, CO. [6] These studies taken together suggest that there is a crucial window when tolerance to gluten occurs and overlapping the introduction of gluten with breastfeeding may provide the best protection against childhood celiac disease. Whether such a practice will prevent the lifetime development of celiac disease or another autoimmune disease ultimately is not known.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Given that the environmental cause of celiac disease is known (gluten) it has been hypothesized that gluten may play an important role in the development of type 1 diabetes. Through prospective studies of high-risk infants for type 1 diabetes and celiac disease, it has been shown that early introduction (prior to 4 months of age) is associated with an increased risk for autoimmunity associated with both conditions (56,57,58). In contrast, diabetes prevention trials using a gluten free diet have not shown any efficacy in delay of diabetes onset (59).…”
Section: Associated Conditions (Table 1)mentioning
confidence: 99%